Soil carbon storage potential of acid soils of Colombia's Eastern High Plains - Hyman, Glenn; Castro, Aracely; Da Silva, Mayesse; Arango, Miguel; Bernal, Jaime; Pérez, Otoniel; Rao, Idupulapati Madhusudana (Frontiers in Sustainable Food Systems, 2022)
Improving soil organic carbon (SOC) storage enhances soil quality and mitigates climate change. Agricultural and livestock specialists increasingly view tropical grasslands as a potential target for storing more soil carbon while boosting productivity. Earlier research in the 1990s showed the promise of improving SOC storage in the Eastern High Plains of Colombia. But these studies were limited to two experimental stations, without focusing on conditions on farms or under variable management. This research examined whether those early studies did indeed reflect possibilities for improving SOC storage and livestock productivity. We measured SOC stocks at one of the experiment stations from previous research and on farms throughout the study area in Colombia's Eastern High Plains. Complementarily our team sampled other predominant land uses to map SOC storage across the nearly 1 million ha study area. Using that information, we also constructed scenarios suggesting changes in SOC and productivity based on land-use changes. The high SOC accumulation found at experimental sites in the 1990s declined 24 years later. However, SOC storage was over 27 Mg ha−1 yr−1 higher than reference native savanna sites, with an accumulation rate of 0.96 Mg ha−1 yr−1. On farms under variable management, improved pastures stored 10 Mg ha−1 more SOC than degraded pastures or native savanna. For the whole region, we estimate that carbon storage observed across soils and land use of the 1 million ha study area could store 0.08 Gt of carbon down to 1 m depth, with wide variation across the region. While the SOC measured in grasslands in the early 1990s did not persist under inadequate management over the period of two decades, the potential to accumulate SOC of Colombia's Eastern High Plains through appropriate management is high, pointing to a sustainable livestock strategy that boosts productivity and reduces emissions.